Determination of hydroxysafflor yellow A in biological fluids of patients with traumatic brain injury by UPLC‐ESI‐MS/MS after injection of Xuebijing. (17th February 2014) - Guo, Yong; Wang, Yang; Huang, Xi.; Lv, Huiying; Fan, Rong; Huang, Wei; Gan, Pingping; Liu, Wei; Yan, Kuipo; Xia, Zian; Liu, Jinfang
ABSTRACT A simple, novel, specific, rapid and reproducible ultra‐performance liquid chromatography electrospray ionization tandem mass spectrometry method has been developed and validated for the determination of hydroxysafflor yellow A (HSYA) in biological fluids (plasma, urine and cerebrospinal fluid) of patients with traumatic brain injury after intravenous injection of Xuebijing (XBJ). Liquid–liquid extraction was performed, and separation was carried out on an Acquity UPLC™ BEH C18 column, with gradient elution using a mobile phase composed of methanol and 0.1% formic acid at a flow rate of 0.3 mL/min. A triple quadrupole tandem mass spectrometer with electrospray ionization was used for the detection of HSYA. The mass transition followed was m/z 611.0 → 491. The retention time was less than 3.0 min. The calibration curve was linear in the concentration range from 2 to 6125 ng/mL for cerebrospinal fluid, plasma and urine. The intra‐ and inter‐day precisions were <10%, and the relative standard deviation of recovery was <15% for HSYA in biological matrices. The method was successfully applied for the first time to quantify HSYA in the biological fluids (especially in cerebrospinal fluid) of patients with traumatic brain injury following intravenous administration of XBJ. Copyright © 2014 John Wiley & Sons, Ltd.